Isotopic investigation of human provenience at the eleventh century cemetery of Ndr. Grødbygård, Bornholm, Denmark - Price, T. Douglas; Naum, Magdalena; Bennike, Pia; Lynnerup, Niels; Frei, Karin Margarita; Wagnkilde, Hanne; Pind, Torben; Nielsen, Finn Ole (Danish Journal of Archaeology, 2012)
Bornholm is a Danish island almost in the center of the southern Baltic Sea. The strategic location of the island, its rich archeology, and its complex geology make it an intriguing location for the isotopic study of past human mobility. The focus of this study is on the large cemetery of Ndr. Grødbygård in the southern part of the island, which dates to the eleventh century AD and contains 553 individuals in 516 graves. The majority of the burials were in a supine position oriented west–east, with the heads to the west, following the tradition of that time. In contrast to the Christian traditions, however, the graves at Grødbygård were richly equipped by Scandinavian standards and some of the burial practices more closely resembled those from the Western Slavic region of the south (present day northeastern Germany and Poland). We have used isotopic analyses to examine the external relations and potential places of origin of the inhabitants of the cemetery. Strontium and oxygen isotope ratios in human tooth enamel provide a signature of place of origin and can be compared to the ratios of the place of burial to determine local or non-local origins. In the case of Bornholm, the local geology is quite complex, with a variety of rocks of different age and composition, resulting in a wide range of strontium isotope sources on the island, complicating the issue of identifying migrants. At the same time, Grødbygård provides an important example of the application of such methods in less than ideal conditions.